2022
DOI: 10.1111/cpr.13250
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effect of high salt on immune cells and related diseases

Abstract: Background: The adverse effect of excessive salt intake has been recognized in decades. Researchers have mainly focused on the association between salt intake and hypertension. However, studies in recent years have proposed the existence of extra-renal sodium storage and provided insight into the immunomodulatory function of sodium.Objectives: In this review, we discuss the modulatory effects of high salt on various innate and adaptive immune cells and immune-regulated diseases. Methods: We identified papers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 243 publications
2
16
1
Order By: Relevance
“…Although this difference was not signi cant, it is consistent with ndings of Isemann et al, who demonstrated Na supplementation of 4 mEq/kg/d during day of life 7-35 signi cantly decreased incidence of late onset sepsis and necrotizing enterocolitis [12]. There are emerging data regarding the impact of Na in the regulation of immune function and the in ammatory response, but whether total body Na status impacts preterm infant infection risk requires further investigation [32,33].…”
Section: Discussionsupporting
confidence: 84%
“…Although this difference was not signi cant, it is consistent with ndings of Isemann et al, who demonstrated Na supplementation of 4 mEq/kg/d during day of life 7-35 signi cantly decreased incidence of late onset sepsis and necrotizing enterocolitis [12]. There are emerging data regarding the impact of Na in the regulation of immune function and the in ammatory response, but whether total body Na status impacts preterm infant infection risk requires further investigation [32,33].…”
Section: Discussionsupporting
confidence: 84%
“…Shaharabani et al noted that myelin phase transition increases with sodium concentrations > 150 millimoles per liter (mmol/L), which is within the range found in vivo [40]. For example, normal serum sodium levels in rodents and humans are approximately 140 mmol/L, but higher sodium concentrations in lymphoid and interstitial tissue range from 160 to 250 mmol/L sodium [48]. Of relevance, serum sodium concentrations are sensitive to fluid overload in hypervolemia, and clinical hyponatremia should be classified as hypervolemic, hypovolemic, or euvolemic [49].…”
Section: Sodium Toxicity and Demyelinationmentioning
confidence: 74%
“…Animal studies have explored various mechanisms of hypertension by combining high salt intake with the intestinal immune response. 23–25 These studies underscore the gut microbiome as a potential therapeutic target for mitigating salt-sensitive diseases. An article published in 2017 first proposed that a high-salt diet affects the gut flora of mice, specifically reducing the abundance of Lactobacillus .…”
Section: High Salt Intake and Public Healthmentioning
confidence: 99%